Lucius artorius marcianus' votive offering to zeus keraunios from the haluk perk museum [Haluk perk miizesi'nden lucius artorius marcianus'un zeus keraunios'a adagi] - (:unkn) unknown (Simurg Kitapclk, Yaynclk ve Datm Ltd. ti., 2013)
This essay presents an inscribed votive offering with the inventory number 604T1 held in the collection of the Haluk Perk Museum in Istanbul. The provenance of the Greek inscription, acquired in 2007, was recorded as from Adana province. The inscription is found on a well- preserved stele. Its translation reads: Lucius Artorius Marcianus, of the Sergian tribe, from Legio XII Keraunophoros (Fulminata), (offered this votive) to Zeus Keraunios. The Legio XII Fulminata ("Casting Thunderbolts") was probably the legio XII recruited by Caesar in 58 BC., which was reformed in 44-43 and then served under Mark Antony. After Actium it was taken over by Caesar Augustus and stationed in Egypt. It was transferred to Syria before A.D. 14, and later its garrison was at Raphaneae. The legion may have been temporarily deployed from Syria to Cappadocia for Corbulo's Armenian campaign of A.D. 57, as it was evidently in Cappadocia when Paetus became governor of that province in 61 and began his ill-fated Armenian campaign. The legio was among the troops of L. Caesennius Paetus, who "shamefully capitulated" in battle against the Parthians. In 66 the legio took part in the failed assault on Jerusalem by the governor of Syria, Cestius Gallus, and later under the command of Titus participated in the siege of Jerusalem. Thereafter Vespasian transferred it to Cappadocia, where it was stationed at Melitene. While at Melitene the Legio XII Fulminata frequently despatched groups of soldiers for service in other parts of Anatolia. It even sent detachments into Armenia under Domitian and again in A.D. 177. The discovery at Adana of an altar dedicated to the legion might indicate diat a detachment of the legion was stationed there at some point in its history. Its loyalty during the revolt of Avidius Cassius in 175 earned it the title of Certa Constans ("the Decisive and Steadfast") from Marcus Aurelius. Its original title was Paterna, which derived from Caesar's honorific title of pater patriae. The absence of the title Certa Constans given by Marcus Aurelius to Legio XII Fulminata in A.D. 175 in this inscription makes it most likely to be dated before this date. The legion was evidently still at Melitene in the late 4th century. The inscription does not indicate where Lucius Aitorius Marcianus came from. But in the Latin epigraphic records the nomen Artorius is found most frequently in Rome and Italy, and in Africa Proconsularis, with a few others in the Balkan regions. This evidence suggests that the origin of Lucius Artorius Marcianus and/or his family is more likely with Italy or Africa or, less likely, with the Balkans. The tribe Sergia is often associated with Roman citizens who originated in Roman military colonies. This suggests a provincial and ultimately military origin for the Roman citizenship of Lucius Artorius Marcianus and/or his family. But more importantly, the tribus was rarely included in inscriptions after A.D. 212 as there was no need for this following the Constitutio Antoniniana.